2021
DOI: 10.3390/medicina57030197
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Stress, Depressive and Anxiety Symptoms in Patients with COPD during In-Hospital Pulmonary Rehabilitation: An Observational Cohort Study

Abstract: Background and Objectives: The relationship between physical health and mental health has been considered for years. A number of studies have shown a correlation between depressive states and the progress of somatic diseases. It seems that the proper cooperation of specialists may result in the improvement of the patient’s well-being and a positive effect on the course of the rehabilitation process. The aim of this study was to assess the symptoms of depression, anxiety, and stress in patients with chronic obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…The higher the total score or the scores in the individual scales, the higher the respondent's stress level. The Sense of Stress Questionnaire has been used in research of, among others, athletes (Makarowski et al, 2020), patients (Wrzeciono et al, 2021), mothers of prematurely born children (Lutkiewicz, 2020), and medical students (Henzel et al, 2016). The scale is characterized by high reliability.…”
Section: Methodsmentioning
confidence: 99%
“…The higher the total score or the scores in the individual scales, the higher the respondent's stress level. The Sense of Stress Questionnaire has been used in research of, among others, athletes (Makarowski et al, 2020), patients (Wrzeciono et al, 2021), mothers of prematurely born children (Lutkiewicz, 2020), and medical students (Henzel et al, 2016). The scale is characterized by high reliability.…”
Section: Methodsmentioning
confidence: 99%
“…[45][46][47] The symptoms of depression and anxiety in COPD lead to worse health outcomes, including impaired health-related quality of life and increased mortality risk. [47][48][49] Meta-analysis results showed that there was no statistical significance of improvement in HADS-A and HADS-D in the singing group compared with the control group. Remarkably, many participants reported relief from adverse mental states, especially for patients who were expert at singing, and these perceived improvements were not reflected in objective outcome measures.…”
mentioning
confidence: 99%
“…Anxiety and depression, as a comorbidity of many diseases, are a complication of chronic obstructive pulmonary disease, and the incidence is higher than other chronic diseases (García and González, 2021;Turnier et al, 2021;Wrzeciono et al, 2021). The two factors of dyspnea and anxiety are mutually stimulating, a vicious circle (Song, 2017).…”
Section: Discussionmentioning
confidence: 99%